Patterns of Road Traffic Accidents in North West of Iran during 2013 New Year Holidays: Complications and Casualties - Shams Vahdati, Samad (Bull Emerg Trauma, 2014)
OBJECTIVE: To determine the patterns,complications and casualties of road traffic accidents in North West of Iran during 2013 New Year holidays. METHODS: One hundred and eighty one patients with trauma-related vehicle crashes were investigated in a cross sectional-descriptive study. We only included those road traffic accidents which were recorded during the 2013 Iranian New Year holidays. Severity of injury based on Glasgow Coma Scale (GCS) score, patient transmission type, damaged organ and the final diagnosis was determined. The mortality rate as well as complications were also recorded and reported. The pattern was analyzed and presented using descriptive statistics. RESULTS: Overall we included 181 patients who were victims of road traffic accidents during the study period. Most cases of multiple traumas were from two car accident (49.2%). Of 181 cases, 71 (39.2%), 66 (36.5%), 16 (8.8%) and 11 (6.1%) subjects had limb, head and neck, abdominal, and spinal cord injuries respectively, while 16 cases (8.8%) did not have any organ damage. In final diagnosis, a limb fracture was noticed in 32 cases (17.7%) and skull fractures in 5 subjects (2.8%) as the first and second causes. CONCLUSION: As head and neck were the most damaged organs after the limbs in patients with multiple traumas, it seems that there is a necessity for these patients in transmission and examination of head traumas. So there is a need for a proper referral system.